Health Diplomacy and Intellectual Property Cooperation within BRICS - Elen de Paula Bueno; Luiza Maria Martins; Maria Antônia Melo Beraldo (Journal of BRICS Studies)
The COVID-19 pandemic highlighted the importance of multilateralism in global health governance, as well as the potential of South-South cooperation on projects aimed at improving health, capacity building and innovation in developing countries. Since the beginning of BRICS and especially from 2011 onwards, the five countries have established strategic partnerships in the areas of health, science, technology, and innovation, resulting in a wide range of exchanges and availability of resources for scientific projects. This paper aims at analyzing the development of BRICS health cooperation, the understanding of its members regarding patent breaking in WTO, as well as the future perspectives on health and science and technology cooperation within the group, especially while considering the BRICS Vaccine Research and Development Centre. In view of the formal establishment of the Vaccine Centre as determined by the BRICS Foreign Affairs Ministers, this article aims at specifying the state of the art of intellectual property cooperation and health diplomacy within BRICS.